Using Co-design With Breast Cancer Patients and Radiographers to Develop “KEW” Communication Skills Training - van Beusekom, Mara; Cameron, Josie; Bedi, Carolyn; Banks, Elspeth; Harris, Rachel; Humphris, Gerry (Frontiers in Psychology, 2021)
Previous work (FORECAST) has shown that concerns of breast cancer patients after finishing radiotherapy are responsive to conversations with radiographers during the treatment period. This study seeks to further understand radiographer and patient experiences, determine shared priorities for improvement in clinical interaction and develop communication guidelines and training to help radiographers support patients. Methods: Using the principles of Experience-Based Co-Design, semi-structured interviews were held with N = 4 patients (videoed) and N = 4 radiographers, followed by feedback events (N = 7) to validate findings. Patients and radiographers exchanged experiences in a joint co-design session, agreed with shared priorities and generated ideas for further support. A survey was conducted for process evaluation. To scale up findings, UK-wide representatives from patient networks (N = 8) and radiographers and managerial staff (N = 16) provided consultative input utilizing an iterative, adaptive procedure. Results: Radiographers expressed a need for support with “difficult conversations,” especially those on Fear of Cancer Recurrence, and their appropriate management. Important pointers for reassuring communication were identified, including: being treated like a person, knowing what to expect, and space to ask questions. The co-design process was rated positively by both staff and patients. Thematic collation of findings and mapping these on literature evidence resulted in the “KEW” communication guidelines for radiographers: Know (Confidence; Expectations; Person), Encourage (Emotions; Space; Follow-up), Warmth (Start; Normalize; Ending). National stakeholder consultations validated and helped fine-tune the training model. The resulting training package, included: trigger videos (n = 6), a simulated patient scenario and interactive handouts on fears of cancer recurrence and the patient pathway. Conclusions: The co-design process captured good practice to help standardize quality in empathic communication in the radiotherapy service. The resulting KEW: Know, Encourage, Warmth guidelines, and training package are user-centered as well as evidence-based. Supplementing single-site co-design with national consultative feedback allows for the development of interventions that are relevant to the clinical practice, even in detail, and helps to generate appropriate buy-in for roll out on a wider scale after evaluation. Trial Registration:www.ClinicalTrials.gov ID: NCT03468881